Hospital readmission within 30 days of older adults hospitalized in a public hospital - Fabiana Silvestre dos Santos; Adriano Max Moreira Reis (Universidade de São Paulo, 2022)
Abstract Older adults have difficulty monitoring their drug therapy in the first thirty days following hospital discharge. This transition care period may trigger hospital readmissions. The study aims to identify the factors associated with the readmission of older adults 30 days after discharge from the perspective of drug therapy. This is a cross-sectional study and hospital admission within 30 days was defined as readmission to any hospital 30 days after discharge. The complexity of the drug therapy was established by the Medication Regimen Complexity Index (MRCI).. Readmission risks were predicted by the "Readmission Risk Score - RRS". The multivariate logistic regression was used to identify factors associated with readmission within 30 days after discharge. Two hundred fifty-five older adults were included in the study, of which 32 (12.5%) had non-elective hospital readmission. A higher number of readmissions was observed with increased RRS value, suggesting a linear gradient effect. The variables included in the final logistic regression model were the diagnosis of cancer (OR=2.9, p=0.031), pneumonia (OR=2.3, p=0.055), and High MRCI (> 16.5) following discharge (OR=1.9, p=0.119). The cancer diagnosis is positively associated with hospital readmissions of older adults within 30 days.